Oblicz wartość liczbową :
a).3a(do potęgi 2) + 3ab
-------------------------------
a(do potęgi 2) + 2ab+b(do potęgi 2)
dla a = - 0,5 b= - 2

B) . a(do potęgi 2)-b(do potęgi 2 )
-----------------------------------------
3a(do potęgi 2 ) - 6ab + 3b (do potęgi 2)
dla a = - 3
b= -1

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T11:31:23+01:00
A)3a² + 3ab
3* (-0,5)²+3* (-0,5)*(-2)
3* 0,25+3
0,75+3=3,75

a²+ 2ab+b²
dla a = - 0,5 b= - 2
(-0,5)²+ 2*(-0,5)*(-2)+(-2)²
0,25+2+4=6,25

B) dla a = - 3
b= -1
a²-b²= (-3)²-(-1)²= 9-1=8

3a²- 6ab + 3b ²=
3*9-6*3+3=27-18+3=6

2010-03-14T11:37:36+01:00
A) 3a²+3ab=6a³+b
a) a²+2ab+b²=(-0.5)+2-0.5-2+(-2)²=-1+2-2.5+4=-1-0.5+4=-1.5+4=2.5
b) a²-b²

3a²-6ab+3b²=3(-3)²-6(-3)*(-1)+3(-1)²=3-9-18+3*1=-24+3=-21